2020
DOI: 10.1097/inf.0000000000002987
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset Neonatal Infections 1997 to 2017 Within a Cohort in Western Sweden—The Last 21 Years of a 43-Year Surveillance

Abstract: Invasive infections affect neonates with the risk of severe morbidity and death, and Streptococcus agalactiae (Group B streptococcus, GBS) remains one of the most common pathogens. The aim of this thesis was to assess infections among neonates and infants, focusing on GBS to better understand prevention and treatment. Clinical data and outcomes were collected from patients' medical records.Paper I was a prospective cohort study of GBS isolates obtained from adults and children with an invasive GBS infection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 245 publications
(379 reference statements)
0
3
0
Order By: Relevance
“…A very comprehensive Swedish retrospective study that encompassed forty-three years of surveillance on LOD (using the case definition of symptoms from 72 h of life onward) demonstrated that GBS-LOD incidence significantly doubled in the last 20 years (from 0.16 to 0.33/1000 livebirths). The increase of infection mostly regarded infants born extremely preterm and it represented the first cause of meningitis [45].…”
Section: Clinical Epidemiology and Risk Factorsmentioning
confidence: 99%
“…A very comprehensive Swedish retrospective study that encompassed forty-three years of surveillance on LOD (using the case definition of symptoms from 72 h of life onward) demonstrated that GBS-LOD incidence significantly doubled in the last 20 years (from 0.16 to 0.33/1000 livebirths). The increase of infection mostly regarded infants born extremely preterm and it represented the first cause of meningitis [45].…”
Section: Clinical Epidemiology and Risk Factorsmentioning
confidence: 99%
“…The risk of EOS increases with the occurrence of chorioamnionitis, prolonged rupture of membranes (i.e., > 18 h before birth) and maternal GBS colonization [ 9 ]. In late-onset sepsis (LOS), symptoms occur at > 72 h of age, the infection is usually hospital-acquired and caused by Gram-positive bacteria (GPB), such as CoNS and Staphylococcus aureus [ 10 12 ]. Low birth weight and gestational age increase the risk of LOS [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In late-onset sepsis (LOS), symptoms occur at > 72 h of age, the infection is usually hospital-acquired and caused by Gram-positive bacteria (GPB), such as CoNS and Staphylococcus aureus [ 10 12 ]. Low birth weight and gestational age increase the risk of LOS [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%